The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1177/073168449701601102
|View full text |Cite
|
Sign up to set email alerts
|

Acid Resistance of Glass Fibre Composites with Different Layup Sequencing: Part I-Diffusion Studies

Abstract: The effects of sulphuric acid concentration and the sequential layup of glass fibre reinforcements on the diffusion behaviour of glass epoxy composite laminates were studied. In all, composites of six different resin systems viz., general purpose polyester, bis phenol-A polyester, vinyl ester, LY 556 epoxy, and MY 750 epoxy resins, reinforced with different layup sequencing consisting of chopped strand mat (CSM) and woven roving mat (WR) were exposed to sulphuric acid environments of different concentrations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…For both solutions, Stamenovic et al [1] concluded that the changes observed on the tensile properties are proportional with the exposure time (number of days in liquid). The effects of sulphuric acid concentration and the sequential layup of glass fibre reinforcements on the diffusion behaviour glass/epoxy laminates were studied by Pai et al [4]. The results showed that composite specimens with chopped strand mat as the skins layers exhibited higher weight gain than those with woven roving mat as the skin layers.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…For both solutions, Stamenovic et al [1] concluded that the changes observed on the tensile properties are proportional with the exposure time (number of days in liquid). The effects of sulphuric acid concentration and the sequential layup of glass fibre reinforcements on the diffusion behaviour glass/epoxy laminates were studied by Pai et al [4]. The results showed that composite specimens with chopped strand mat as the skins layers exhibited higher weight gain than those with woven roving mat as the skin layers.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The results showed that composite specimens with chopped strand mat as the skins layers exhibited higher weight gain than those with woven roving mat as the skin layers. Material degradation is more pronounced with the increase of sulphuric acid concentration, which can be explained by hydrolytic dissolving of the matrix in contact with this acid [1,4]. Degradation studies were carried out in different solvents like 10% NaOH, 1 N HCl and 10% NaCl by Sindhu et …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Pai et al (1997) 14,15 studied the performance of laminated composites under service conditions by focusing on the interlaminar shear strength (ILSS), which is a resin-dominated property. The authors subjected two different types of polyesters, a vinyl ester, and three epoxy resins to 15%, 25%, and 30% sulphuric acid solutions for 5 months.…”
Section: Literature Review: Durability Of Isophthalic Polyestermentioning
confidence: 99%
“…Specimens cut from the pipes were immersed for various periods -30, 60, and 90 days in 20% acid concentration at room temperature and 100°C. The effects of sulphuric acid concentration and the sequential lay-up of glass fibre reinforcements on the diffusion behaviour of glassepoxy composite laminates were studied in [5]. Experimental results for the direct effect of an acidic stress environment on the stress intensity factor of woven E-glass fibre reinforced bisphenol-vinylester resin, woven E-glass fibre reinforced bisphenolepoxy resin and woven C-glass fibre reinforced bisphenol-vinylester resin composites are presented in [6].…”
mentioning
confidence: 99%